Cigarette Smoke Extract Inhibits Platelet Aggregation by Suppressing Cyclooxygenase Activity - Kashiwagi, Hitoshi; Yuhki, Koh-ichi; Imamichi, Yoshitaka; Kojima, Fumiaki; Kumei, Shima; Higashi, Tsunehito; Horinouchi, Takahiro; Miwa, Soichi; Narumiya, Shuh; Ushikubi, Fumitaka (TH Open, 2017)
The results of studies that were performed to determine whether cigarette smoking affects platelet function have been controversial, and the effects of nicotine- and tar-free cigarette smoke extract (CSE) on platelet function remain to be determined. The aim of this study was to determine the effect of CSE on platelet aggregation and to clarify the mechanism by which CSE affects platelet function. CSE inhibited murine platelet aggregation induced by 9,11-dideoxy-9α,11α-methanoepoxy-prosta-5Z,13E-dien-1-oic acid (U-46619), a thromboxane (TX) A2 receptor agonist, and that induced by collagen with respective IC50 values of 1.05 ± 0.14% and 1.34 ± 0.19%. A similar inhibitory action of CSE was also observed in human platelets. CSE inhibited arachidonic acid–induced TXA2 production in murine platelets with an IC50 value of 7.32 ± 2.00%. Accordingly, the inhibitory effect of CSE on collagen-induced aggregation was significantly blunted in platelets lacking the TXA2 receptor compared with the inhibitory effect in control platelets. In contrast, the antiplatelet effects of CSE in platelets lacking each inhibitory prostanoid receptor, prostaglandin (PG) I2 receptor and PGE2 receptor subtypes EP2 and EP4, were not significantly different from the effects in respective control platelets. Among the enzymes responsible for TXA2 production in platelets, the activity of cyclooxygenase (COX)-1 was inhibited by CSE with an IC50 value of 1.07 ± 0.15% in an uncompetitive manner. In contrast, the activity of TX synthase was enhanced by CSE. The results indicate that CSE inhibits COX-1 activity and thereby decreases TXA2 production in platelets, leading to inhibition of platelet aggregation.
Keywords: cigarette smoke extract; platelets; thromboxane A2; cyclooxygenase